Structure of soil biocoenosis and biodiversity in olive orchards of three eastern Mediterranean islands - Liantraki, Z.; Tzokas, I.; Kollaros, D. (ENTOMOLOGIA HELLENICA, 2014)
In this work the structure of soil arthropods’ biocoenosis was compared among 11 olive orchards from six localities of Crete (three of the localities from Messara’s valley, including two olive orchards each one, plus three localities near to Herakleion city) and other two ones each from the island of Kos and Cyprus. Pitfall traps were used and totally 35 taxa were captured. The order Coleoptera and the family Formicidae were the two main taxa at the 8 of the 11 olive orchards. Statistically significant differences in biodiversity were recorded among the orchards separating them in three groups, the first group included Messara’s olive orchards, the second the olive orchards of the rest of the Crete and the third group the olive groves of the other two islands. Messara’s group had higher biodiversity than the third group. By studying the similarities of biological communities, some pairs of Messara’s olive groves, have the highest ones. Among the 15 highest values, the 14 belonged to pairs between Messara’s olive orchards. Generally, biocoenosis in all 11 olive orchards of the three different islands follows a similar pattern, despite of differences in cultural practices and changes of climatic factors from a year to another.